Pengembangan ICU Card Talk sebagai Alat Bantu Komunikasi bagi Pasien dengan Ventilasi Mekanik - Soemiati Soemiati; Joni Haryanto; Christijogo Sumartono (Journal of Telenursing (JOTING), 2023)
This study aims to develop ICU Card Talk as a communication tool for mechanically ventilated patients. The method used in this study was a Research and Development approach with data collection stages through literature studies, interviews, and observations to formulate strategic issues and design ICU Card Talk content designs through focus group discussions based on strategic issues. The results of this study are color graphic communication cards equipped with writing according to the patient's basic needs and patient complaints measuring 10x15 cm using a glossy paper. The results of the content validity test by assessing the I-CVI showed that the ICU Card Talk content was valid with a value of 1.0, and the reliability value obtained a reliability coefficient > 0.6 which stated that the ICU Card Talk content was reliable. In conclusion, ICU Card Talk can be used as a communication tool that is easy to use as a means of interaction between patients with mechanical ventilation and medical staff so that patient communication needs can be met. This will indirectly reduce the patient's stress level, which will affect the patient's recovery. Keywords: Intensive Care, Communication, Mechanical Ventilation